Prospective observational study of postoperative infection and outcomes after noncardiac surgery: analysis of prospective data from the VISION cohort. (July 2020) - Wan, Yize I.; Patel, Akshaykumar; Abbott, Tom E.F.; Achary, Cheryl; MacDonald, Neil; Duceppe, Emmanuelle; Sessler, Daniel I.; Szczeklik, Wojtek; Ackland, Gareth L.; Devereaux, Philip J.; Pearse, Rupert M.
Abstract: Background: Infection is a frequent cause of postoperative morbidity and mortality. The incidence, risk factors, and outcomes for postoperative infections remain poorly characterised. Methods: This is a secondary analysis of a prospective international cohort study of patients aged ≥45 yr who had noncardiac surgery (VISION), including data describing infection within 30 days after surgery. The primary outcome was postoperative infection. The secondary outcome was 30 day mortality. We used univariable and multivariable logistic regression to identify baseline risk factors for infection. Results are presented as n (%) or odds ratio (OR) with 95% confidence intervals. Some denominators vary according to rates of missing data. Results: Among 39 996 surgical patients, 3905 (9.8%) experienced 5152 postoperative infections and 715 (1.8%) died. The most frequent infection was surgical site infection (1555/3905 [39.8%]). Infection was most strongly associated with general surgery (OR: 3.74 [3.11–4.49]; P <0.01) and open surgical technique (OR: 2.03 [1.82–2.27]; P <0.01); 30 day mortality was greater amongst patients who experienced infection (262/3905 [6.7%] vs 453/36 091 patients who did not [1.3%]; OR: 3.47 [2.84–4.22]; P <0.01). Mortality was highest amongst patients with CNS infections (OR: 14.72 [4.41–49.12]; P <0.01). Conclusions: Infection is a common and important complication of noncardiac surgery, which is associated with high mortality. Further research is needed to identify more effective measures to prevent infections after surgery.